The Role of Hemosiderin Excision in Seizure Outcome in Cerebral Cavernous Malformation Surgery: A Systematic Review and Meta-Analysis - Ruan, Di; Yu, Xiao-Bo; Shrestha, Sudeep; Wang, Lin; Chen, Gao (PloS one, 2015)
Whether the excision of hemosiderin surrounding cerebral cavernous malformations (CCMs) is necessary to achieve a seizure-free result has been the subject of debate. Here, we report a systematic review of related literature up to Jan 1, 2015 including 594 patients to assess the effect of hemosiderin excision on seizure outcome in patients with CCMs by meta-analysis. Ten studies comparing extended hemosiderin excision with only lesion resection were identified by searching the English-language literature. Meta-analyses, subgroup analyses and sensitivity analysis were conducted to determine the association between hemosiderin excision and seizure outcome after surgery. Seizure outcome was significantly improved in the patients who underwent an extended excision of the surrounding hemosiderin (OR, 0.62; 95% CI: 0.42-0.91; P = 0.01). In subgroup analysis, studies from Asia (OR, 0.42; 95% CI: 0.25-0.71; P = 0.001), male-majority (female ratio < 50%) studies (OR, 0.56; 95% CI: 0.33-0.96; P = 0.04), low occurrence rate of multiple CCMs (OR, 0.37; 95% CI: 0.20-0.71; P = 0.003), cohort studies (OR, 0.44; 95% CI: 0.28-0.68; P = 0.78), longer duration of seizure symptoms (> 1 year) before surgery (OR, 0.43; 95% CI: 0.22-0.84; P = 0.01), lesion diameter > 2 cm (OR, 0.41; 95% CI: 0.19-0.87; P = 0.02) and short-term (< 3 years) follow-up (OR, 0.48; 95% CI: 0.29-0.80; P = 0.005) tended to correlate with a significantly favorable outcome. Patients who underwent extended surrounding hemosiderin excision could exhibit significantly improved seizure outcomes compared to patients without hemosiderin excision. However, further well-designed prospective multiple-center RCT studies are still needed.